Effects of environmental conditions on planktonic abundances, benthic recruitment and growth rates of the bivalve mollusc Ruditapes decussatus in a Portuguese coastal lagoon - Chícharo, Luís (2013)
Controlling environmental parameters for the early stages of marine invertebrates have received little attention, particularly in field studies. This study involves measurement of abundances and growth rates of the bivalve Ruditapes decussatus Linnaeus 1758 during its planktonic larval and early benthic life stages in a coastal lagoon: Ria Formosa, Portugal. Measured abundances were compared with tidal amplitude, water temperature, salinity, wind velocity and direction, and a food availability indicator 2chlorophyll a). Data were obtained on abundance and prodissoconch length of the larvae, measured two tothreetimes perweek,and ofpost-larval stagesindividuals thathadsettled inartificial collectors over10months.Larval and juvenile cohorts were identified using size-frequency distributions and larval ages estimated by larval shell growth lines.